METİLPREDNİSOLON VE MELOKSİKAM'IN İNTRAABDOMİNAL ADEZYONLARIN ÖNLENMESİ ÜZERİNE ETKİLERİ - GÜNDÜZ, ÖMER FARUK (Fırat Üniveristesi, 2019)
Bu çalışmada intraabdominal adezyonların önlenmesinde meloksikam ve metilprednizolon'un etkilerinin araştırılması amaçlanmıştır. Çalışmada 21 adet 2-3 aylık dişi Wistar albino rat kullanıldı. Ratlar her grupta 7 adet olacak şekilde 3 gruba ayrıldı. Genel anestezi altında karın altında yaklaşık olarak 2 cm uzunluğunda laparotomi gerçekleştirildi. Karın duvarı ve sekumun visceral yüzeyinde serosal kanama oluşana kadar kazıma işlemi yapılarak bir yapışma modeli oluşturuldu. Operasyon yaraları rutin cerrahi kurallara göre kapatıldı. Birinci, 2. ve 3. gruptaki ratlara 5 gün süreyle intraperitoneal olarak sırasıyla 7 ml/kg serum fizyolojik (kontrol), 5 mg/kg meloksikam ve 10 mg/kg metilprednizolon enjekte edildi. Ondört gün sonra ratlar genel anestezi altına alınarak oluşan adezyonlar değerlendirildi. Makroskopik değerlendirmede tedavi gruplarında adezyon oluşumu kontrol grubuna göre daha az olarak gözlendi (P<0.05). Yapılan histopatolojik kontrollerde, yangı şiddeti kontrol grubunda daha belirgindi. Fibrozis en belirgin olarak kontrol grubunda gözlendi (P<0.05). İmmunohistokimyasal değerlendirmelerde IL1 pozitif hücre sayısının kontrol grubunda tedavi gruplarına göre daha fazla olduğu belirlendi (P<0.05). Sonuç olarak intraabdominal adezyonların önlenmesinde meloksikam ve metilprednizolon'un kullanılabileceği kanısına varılmıştır.

In this study, it was aimed to investigate the effects of meloxicam and methylprednisolone on the prevention of intraabdominal adhesions. Twenty-one 2-3 month old female Wistar albino rats were used in the study. The rats were divided into 3 groups as 7 rats in each group. Under general anesthesia, approximately 2 cm long laparotomy was performed under the abdomen. An adhesion model was formed by performing scraping process on the visceral surface of the abdominal wall and caecum until serosal hemorrhage occurred. Operation wounds were closed according to routine surgical rules. Seven mL/ kg saline (control), 5 mg / kg meloxicam and 10 mg / kg methylprednisolone were injected intraperitoneally to the rats in the first, second and third groups for 5 days respectively. After 14 days, rats received general anesthesia and occured adhesions were graded. Fourteen days later, the rats were placed under general anesthesia and if any the adhesions were evaluated. In macroscopic evaluation, adhesion formation in treatment groups was less than in the control group (P<0.05). In the histopathological examination, the severity of the inflammation was more marked in the control group. Fibrosis was most significantly observed in the control group (P<0.05). In immunohistochemical evaluation revealed that IL1 positive cell number was much in the control group than in the treatment groups (P<0.05). As a result, it was concluded that meloxicam and methylprednisolone could be used in the prevention of intraabdominal adhesions.
Effects of methylprednisolone and meloxicam on the prevention of intraabdominal adhesions
Keywords: Veteriner Hekimliği